Evaluation of interface shear strength properties of geosynthetic with Recycled concrete and Asphalt waste by direct shear test - H. Heiraty; M. Hassanlourad; A.R. Ardakani (مهندسی عمران شریف, 2022)
Granular materials are widely used in construction. The cost and environmental impact of supplying natural aggregates force the construction industry to look for alternative materials for engineering applications. The interface shear strength properties of recycled construction materials including concrete and asphalt with geogrid as alternative backfill materials in reinforced structures were investigated by using Large-scale Direct Shear Test (LDST) apparatus. Also, a comparison is made between the recycled materials and a natural material with the same physical characteristics and grain size. Geosynthetics are mainly used to stabilize and reinforce different types of earth structures such as slopes, retaining walls, bridge abutments, and foundations. In these cases, the interaction between soil and geosynthetic has a vital role. Three types of single-stranded geogrids were tested as reinforcements. The results showed that reinforcement increases the shear strength and internal friction angle. The tensile strength of geogrids does not have effect on the interface shear strength as the geogrids do not reach the failure state during shear test. The shear strength coefficient for these materials was greater than one, which indicates a strong interaction between the geogrid and the materials. Recycled materials including concrete and crushed asphalt have good shear strength and can be used as an alternative to natural materials in reinforced soil retaining walls, although their shear behavior is slightly different. In general, due to the involvement of these aggregates with the geogrid, it leads to an increase in the shear strength of the interface of these materials and the geogrid to the materials themselves. The shear behavior of natural materials and concrete changes from a slightly softening behavior to a hardening behavior on the interface, a process that is more severe in the case of asphalt. Also, the volumetric behavior of the interface of natural materials and recycled concrete with geogrid is more extensive than the materials themselves, the opposite is true for asphalt. Recycled asphalt materials have a lower interaction coefficient than natural materials and recycled concrete. This reason could be attributed to bitumen coating on recycled asphalt aggregates. In general, recycled concrete and asphalt materials provide the minimum shear strength parameters when reinforced with geogrids.